Laser Treatment to form An Effective Base Contact in a - Si:H/c-Si Heterojunction Solar Cells. (December 2015) - Serenelli, Luca; Izzi, Massimo; Chierchia, Rosa; Tucci, Mario
Abstract: In this paper we investigate the p-type a-Si:H/ia-Si:H/p-type c-Si structure, commonly used as base contact in amorphous/crystalline silicon heterojunction solar cell when fabricated on p-type c-Si wafer. Even though the most effective amorphous silicon/crystalline silicon heterostructure is based on n-type c-Si due to higher bulk lifetime, the p-type c-Si still remains the most common and cheaper substrate for silicon based solar cell. In particular we study the effect of localized 532 nm pulsed laser treatment at different laser conditions in order to reduce the cell series resistance due to the base contact. In this approach the p-type a-Si:H layer is used as a source of boron dopant. Depending on the thickness of the p-type a-Si:H film, when the laser beam is focused on p-type a-Si:H layer the boron can be transferred into the c-Si base to form an overdoped region and then an effective local Back Surface Field, able to enhance the hole collection at the metal of the base electrode in the p-type c-Si based heterojunction solar cell. The application of a thin Aluminum layer on top of the amorphous silicon to be treated by laser is also concerned. Series resistance of a transverse structure composed by the laser treated p-type a-Si:H/c-Si/opposite surface contacted by InGa is considered to optimize the laser procedure. Values as low as 0.5 Ωcm 2 are obtained when the aluminum layer is adopted.